The Semantic Web: ESWC 2012 Satellite Events ESWC 2012 Satellite Events, Heraklion, Crete, Greece, May 27-31, 2012. Revised Selected Papers - Simperl, Elena.; Simperl, Elena.; Norton, Barry.; Norton, Barry.; Mladenic, Dunja.; Mladenic, Dunja.; Della Valle, Emanuele.; Della Valle, Emanuele.; Fundulaki, Irini.; Fundulaki, Irini.; Passant, Alexandre.; Passant, Alexandre.; et al. (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2015)
This book constitutes the thoroughly refereed post-proceedings of the satellite events of the 9th International Conference on the Semantic Web, ESWC 2012, held in Heraklion, Crete, Greece, in May 2012. This volume contains 49 full papers  and 13 short papers describing the posters and demonstrations. (SUGGESTION/ HELP  needed).